A Near‐Infrared Photoactive Morphology Modifier Leads to Significant Current Improvement and Energy Loss Mitigation for Ternary Organic Solar Cells. Issue 8 (20th June 2018) - Zhan, Lingling; Li, Shuixing; Zhang, Huotian; Gao, Feng; Lau, Tsz‐Ki; Lu, Xinhui; Sun, Danyang; Wang, Peng; Shi, Minmin; Li, Chang‐Zhi; Chen, Hongzheng
Abstract: Herein, efficient organic solar cells (OSCs) are realized with the ternary blend of a medium band gap donor (poly[(2, 6‐(4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)‐benzo[1, 2‐b:4, 5‐b′]dithiophene))‐alt‐(5, 5‐(1′, 3′‐di‐2‐thienyl‐5′, 7′‐bis(2‐ethylhexyl)benzo[1′, 2′‐c:4′, 5′‐c′]dithiophene‐4, 8‐dione)] (PBDB‐T)) with a low band gap acceptor (2, 2′‐((2Z, 2′Z)‐(((2, 5‐difluoro‐1, 4‐phenylene)bis(4, 4‐bis(2‐ethylhexyl)‐4H‐cyclopenta[2, 1‐b:3, 4‐b′]dithiophene‐6, 2‐diyl))bis(methanylylidene))bis(5, 6‐difluoro‐3‐oxo‐2, 3‐dihydro‐1H‐indene‐2, 1‐diylidene))dimalononitrile (HF‐PCIC)) and a near‐infrared acceptor (2, 2′‐((2Z, 2′Z)‐(((4, 4, 9, 9‐tetrakis(4‐hexylphenyl)‐4, 9‐dihydro‐s‐indaceno[1, 2‐b:5, 6‐b′]dithiophene‐2, 7‐diyl)bis(4‐((2‐ethylhexyl)oxy)thiophene‐5, 2‐diyl))bis(methanylylidene))bis(5, 6‐difluoro‐3‐oxo‐2, 3‐dihydro‐1H‐indene‐2, 1‐diylidene))dimalononitrile (IEICO‐4F)). It is shown that the introduction of IEICO‐4F third component into PBDB‐T:HF‐PCIC blend increases the short‐circuit current density ( J sc ) of the ternary OSC to 23.46 mA cm −2, with a 44% increment over those of binary devices. The significant current improvement originates from the broadened absorption range and the active layer morphology optimization through the introduction of IEICO‐4F component. Furthermore, the energy loss of the ternary cells (0.59 eV) is much decreased over that of the binary cells (0.80 eV) due to the reduction of both radiative recombination from the absorption below the band gap and nonradiative recombination upon the addition of IEICO‐4F. Therefore, the power conversion efficiency increases dramatically from 8.82% for the binary cells to 11.20% for the ternary cells. This work provides good examples for simultaneously achieving both significant current enhancement and energy loss mitigation in OSCs, which would lead to the further construction of highly efficient ternary OSCs. Abstract : Near‐infrared nonfullerene acceptor of IEICO‐4F is introduced to a polymer donor:acceptor, PBDB‐T:HF‐PCIC, blend. A recorded current enhancement of 7.2 mA cm −2 and a reduced energy loss of 0.59 eV are achieved for the ternary solar cells. Thus, power conversion efficiency is improved significantly from 8.82% for binary cells to 11.20% for ternary cells.